2017
DOI: 10.1371/journal.pone.0185434
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of Borrelia burgdorferi sensu lato – An analytical comparison of real-time PCR protocols from five different Scandinavian laboratories

Abstract: IntroductionLyme borreliosis (LB) is the most common tick transmitted disease in Europe. The diagnosis of LB today is based on the patient´s medical history, clinical presentation and laboratory findings. The laboratory diagnostics are mainly based on antibody detection, but in certain conditions molecular detection by polymerase chain reaction (PCR) may serve as a complement.AimThe purpose of this study was to evaluate the analytical sensitivity, analytical specificity and concordance of eight different real-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 31 publications
2
32
0
1
Order By: Relevance
“…All samples were analyzed by two independent PCR assays, and no sample was classified as positive for B. burgdorferi sensu lato DNA based on a single PCR. We consider the risk of false-positive results with these methods to be low, in accordance with the previous validation of these assays (26,27).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…All samples were analyzed by two independent PCR assays, and no sample was classified as positive for B. burgdorferi sensu lato DNA based on a single PCR. We consider the risk of false-positive results with these methods to be low, in accordance with the previous validation of these assays (26,27).…”
Section: Discussionsupporting
confidence: 61%
“…The following thermocycling parameters were used on a LightCycler 480 system: 2 min at 40°C followed by 10 min at 95°C and 47 cycles of 15 s at 95°C, 30 s at 60°C, and 20 s at 72°C. The ospA and 16S rRNA gene real-time assays used in this study have been validated against several panels of Borrelia strains in order to document the ability to detect strains relevant to human disease (26). The specificity of the assays has been challenged by testing DNA extracted from Ͼ130 CSF samples from adult non-LB controls (27) without generating any false-positive results.…”
Section: Methodsmentioning
confidence: 99%
“…The ospA gene is also a commonly used target for PCRanalysis. However, previous studies have shown that protocols for detecting ospA are unable to detect the species B. spielmanii and B. miyamotoi, both of which are known to be pathogenic to humans 189 .…”
Section: Borrelia Proteins Genes and Their Function As Diagnostic Tmentioning
confidence: 98%
“…Assays based in flagellin should therefore preferably be used as a recombinant truncated internal fragment 22,50 . The flaB gene is also used as a target in PCRanalysis and has been proven to detect all pathogenic strains 189 .…”
Section: Borrelia Proteins Genes and Their Function As Diagnostic Tmentioning
confidence: 99%
See 1 more Smart Citation